1986
DOI: 10.2136/sssaj1986.03615995005000030020x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fertilizer Source on Denitrification and Nitrous Oxide Emissions in a Maize‐field

Abstract: The C2H2‐block method was used to measure denitrification in a maize (Zea mays L.) field over the 85‐d period between sidedressing with N fertilizer and harvest. Measurement locations were changed weekly in order to avoid problems associated with microbial utilization of C2H2 and inhibition of nitrification. Nitrous oxide (N2O) fluxes were measured both with and without C2H2 addition to soil. Without C2H2 addition to soil, 0.3 kg N ha−1 was evolved from both unfertilized and Ca(NO3)2 treated soil, whereas 2.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(27 citation statements)
references
References 0 publications
3
24
0
Order By: Relevance
“…The sampling depth is unlikely to have appreciably influenced the results, as denitrification activity is usually concentrated in the surface soil (Aulakh et al, 1992;Ryden et al, 1987). The CVs reported here (average value of 47%) are within the range commonly reported for denitrification measurement; for example, Duxbury and McConnaughey (1986) reported CVs of 50-60%, and Thompson et al (1987) and Thompson (1989) reported CVs of > 100% when using a similar core incubation method but with two replicate jars per measurement. While the average CV reported here is appreciable, it is worth noting that consistent differences were maintained between treatments.…”
Section: Denitrification Losssupporting
confidence: 68%
“…The sampling depth is unlikely to have appreciably influenced the results, as denitrification activity is usually concentrated in the surface soil (Aulakh et al, 1992;Ryden et al, 1987). The CVs reported here (average value of 47%) are within the range commonly reported for denitrification measurement; for example, Duxbury and McConnaughey (1986) reported CVs of 50-60%, and Thompson et al (1987) and Thompson (1989) reported CVs of > 100% when using a similar core incubation method but with two replicate jars per measurement. While the average CV reported here is appreciable, it is worth noting that consistent differences were maintained between treatments.…”
Section: Denitrification Losssupporting
confidence: 68%
“…processed by nitrification) would be expected, corresponding to 10.5 lg N 2 O-N kg -1 day -1 , which would have been below the level of detection in our system. The IPCC emission factor of 1.25% includes emissions from both nitrification and denitrification and estimates from Subbarao et al (2006) suggest that emissions from nitrification rarely exceed 2% and only exceptionally reach 4% (Duxbury and McConnaughey 1986).…”
Section: Resultsmentioning
confidence: 99%
“…They found N 2 O emission from maize fields ranged from 0.5 to 7.3% of N applied compared with 0.1-1.0% of N applied from fallow fields. Duxbury and McConnaughey (1986) found total gaseous N loss during corn growth was less than 3% of the applied N, and loss of N as N 2 O during nitrification of NH 4 + was not a major route of N loss.…”
Section: N Application Effectmentioning
confidence: 86%